Effect of Liquidity Ratio and Solvency Ratio As Well As Rentability to Value Ratio of Cement Companies - Leny Susilawati Angraini; Jumri Jumri (Budapest International Research and Critics University, 2021)
The purpose of this study is to determine the effect of current ratio and debt to equity ratio on price to book value through mediation of return on assets in cement sub-sector companies listed on the Indonesia Stock Exchange in the period 2013-2017. The sample used in this study is a group of cement sub-sector companies listed on the Indonesia Stock Exchange, which total 5 cement companies and have been listed on the IDX in the period 2013-2017. The analytical techniques used are with linear regression equations, coefficients of determination, test F, and test T. Data is analyzed with the help of SPSS software. The results of the analysis obtained, current ratio, debt to equity ratio and return on assets have a significant effect on price to book value in the cement sub-sector on the Indonesia Stock Exchange, in addition debt to equity ratio is the most dominant variable.